Community-Based Mentoring for Resident Physicians - Adam Sharp; Amy Sharp; Jennifer Walthall (Association of American Medical Colleges, 2011)
Abstract Introduction Preventive medicine can be approached in various ways, all with the purpose of avoiding illness or injury before it occurs. Physicians can use their position of influence, clinical skills, and medical expertise to promote healthy lifestyles. Evidence supports the utility of mentoring programs in decreasing violent behaviors and improving self-efficacy. Emergency medicine physicians and residents at the Indiana University School of Medicine developed a mentoring program in conjunction with an after-school program from Indianapolis Public Schools. Methods As part of this mentoring program, a notebook was created for both mentor and student. The notebook was founded on Benjamin Franklin's 13 core values: temperance, silence, order, resolution, frugality, industry, sincerity, justice, moderation, cleanliness, chastity, tranquility, and humility. It helped guide discussion and was used to aid busy physicians/residents in mentoring high-risk adolescents in a structured format. The program also featured a set of lessons intended to encourage interaction between students and mentors regarding important topics affecting health. These topics included nutrition, communication, organizational skills, and conflict management. The program and notebook were designed to prevent commonly encountered injuries and illnesses and to educate resident physicians regarding community-based programs and doctor-patient relationships. Results Since the program's inception in 2006, 57 students, 35 resident mentors, and three staff physicians have participated. Our experience indicates that the program has been effective at improving the ability of physicians to communicate with patients, educating residents in how to work with community partners, and promoting professional behaviors in resident physicians. Discussion Our mentoring notebook was not created to scientifically evaluate the efficacy of mentoring but as an aid to facilitate mentoring. It has been used successfully in a physician-organized mentoring program designed as a tool for residency education.